Idāratu Barnāmaj Daurah Al-Lughah Al- ‘Arabiyyah Al- Mukatstsafah Omar Smart Brain (OSB) Learning Centre - Arini Elhaq; Nuril Mufidah; Abdul Malik Karim Amrullah (Uktub: Journal of Arabic Studies, 2022)
The success of implementing a program is affected by the management of that programme. The aim of this research is to 1) describe the implementation of the Omar Smart Brain (OSB) Learning Center Intensive Arabic Language Program, 2) describe the evaluation of this program, and 3) reveal the supporting and hindering factors in it. This research used the qualitative approach of the case study method. Data was described through the results of observation, interview, books, periodicals, media and the international network. The results are: 1) The implementation of this course under the supervision of the teacher and the administrator, with the aim of teaching the Arabic using the Arabiyyah Bayna Yadaik book for mothers and young women by the audio-visual method in two and a half years, 2) The evaluation is by examining each after the completion of two units and after five months, 3) The supporting factors are the quality of the teaching environment, the teacher's competence, the students' enthusiasm and self-confidence, and the obstacles are the weak ability of the students to read and write Arabic, the diverse backgrounds of the students, the teacher jobs, and the presence of the Covid-19 pandemic. In conclusion, the management of the OSB Learning Center Intensive Arabic Course is a good management.